Enhancing the Properties of Concrete Mixture for Construction by Partially Replacing Mangrove Charcoal in Cement and Including Sawdust as an Additive with Sand - THARSVINDRAN A/L RAJENDIRAN; Mohamd Luthfi Ahmad Jeni (Progress in Engineering Application and Technology, 2025)
This study explores the use of mangrove charcoal and sawdust in concrete making to improve sustainability and reduce environmental impact such as release of carbon emission due to cement manufacturing and health problem and air pollution that caused from poor waste management of sawdust. This lightweight concrete’s mechanical qualities are compared to conventional concrete using slump, water absorption, concrete density, and compressive strength tests. The study’s objectives are to assess the mechanical properties and durability of concrete mixtures with partially replaced cement with mangrove charcoal and sawdust added to sand and also to find the ideal percentage of substitution and additional material in the concrete mixture. The results from all the test showed, when the percentage of mangrove charcoal and sawdust increased, the value of compressive strength, workability, water absorption and density of the concrete, decreased perpendicularly after both 7 and 28 days of curing. But the appropriate usage of these materials in concrete mixture, contributes in producing high quality concrete and reduces the demand of natural resources in the construction sector while promoting the utilization of waste.